Menaklukkan Perubahan: Faktor-Faktor Kesiapan Berubah pada Pekerja Indonesia di Era Modern - Putu Eka Natasha Angolina Putri; Firmanto Adi Nurcahyo (Jurnal Riset Multidisiplin Edukasi, 2025)
In the era of globalization, intense business competition compels companies to swiftly adapt to environmental changes. The preparedness of individuals within the organization plays a crucial role in confronting these changes. However, individuals' readiness is often overlooked, despite its significant impact on employees' attitudes and responses to organizational changes. This literature study explores the factors influencing individuals' readiness to face changes and strategies employed by companies to enhance it. Employing a quantitative literature study method, this research analyzes 10 selected scholarly articles as data sources through content analysis. The findings of this study are anticipated to provide in-depth insights into individuals' readiness to change and aid companies in developing effective strategies to manage organizational changes.